Regional Peer Effects of Corporate Tax Avoidance - Gao, Ya; Cai, Chang; Cai, Yiwei (Frontiers in Psychology, 2021)
This study empirically shows that there is a significant regional peer effects in tax avoidance. We use the stock idiosyncratic return of peer companies as an instrumental variable to solve potential endogenous problems. Furthermore, after conducting the heterogeneity analysis, it indicates that the stronger the intensity of regional tax collection and management, the higher the degree of informatization, the more similar the size and age of enterprises in the same region, and the more significant the regional peer effects among non-state-owned enterprises. Finally, we find that manager information learning, manager reputation concern, manager information communication are mechanisms of peer effects. The research of this paper finds that there are significant regional peer effects of corporate tax avoidance, which provides a new collection and management idea for tax authorities to supervise corporate tax avoidance.